232 UNRAVELING THE BARRIERS TO EXCELLENCE IN RESIDENTS' TEACHING: A NEEDS ASSESSMENT USING THE NOMINAL GROUP TECHNIQUE TO IDENTIFY CONTENT AND FORMAT FOR A RESIDENTS AS TEACHERS AND LEADERS (RATL) PROGRAM. Issue 1 (1st January 2007) - Tejada-Simon, M. V.; Ismail, N.; Culberson, J. W.; Patton, C. S.; Friedland, J. A.; Dewey, C. M.
Abstract : Purpose: Residents are responsible for the majority of medical student teaching and directly supervise, instruct, and evaluate students. Residents also serve as important role models. The LCME and other organizations now recommend that resident training programs include more venues specifically designed to develop resident teaching skills. To create a Residents as Teachers and Leaders (RATL) Program that may be applied across all resident specialty training, we used a nominal group technique (NGT) to identify and rank the content and best delivery format for such a program. Methods: We enlisted the help of all seven core student rotation residency program directors from Baylor College of Medicine. They recommended new PGY 2 residents from each program to make up an interdisciplinary group of residents to participate in a small-group needs assessment using NGT. The 2-hour session was composed of part 1, a large group overview, and part 2, two small groups using an NGT focusing on either content or format. Residents were randomly assigned to either the content or format group. Results: Sixteen new PGY 2 residents participated in the 2-hour session and represented residency programs in internal medicine, pediatrics, surgery, and psychiatry. Nine residents participated in the content group and seven residents in the format group. The content group identified 52 items, clarified and grouped these items into 50, and ranked 26. They ranked items as important and necessary in a RATL program. The format group identified 38 items clarified and grouped them 15 and ranked and regrouped 9 items into 3. Residents identified 12 items and ranked 3 items they wish to exclude. Conclusions: Using an NGT, we identified key content areas and formatting issues to help in the development of a RATL program for Baylor. This technique was very effective in generating ideas and ensuring equal participation within the group and equal representation of each member's opinions.